DAKWAH DAN FENOMENA KEKERASAN DALAM RUMAH TANGGA - Siti Nurul Yaqinah (TASÂMUH, 2018)
The behavior of domestic violence is a tendency of behavior that is not in accordance with human nature and not in accordance with Islamic teachings. The causes of domestic violence can be classified into two factors, internal and external factors. Internal factors concerning the personality of the perpetrators of violence that makes it very easy to commit violence when faced with situations that cause anger or frustration. External factors are factors outside the abuser's self. For example economic difficulties, infidelity husband or wife, child and so forth. To minimize cases of domestic violence, the da'wah perpetrators promoted counselling of community-based da'wah, for example by promoting education on human rights and women's empowerment, and to socialize gender equality. Equally important is to build a mosque-based community economy and empower the work ethic of Muslims. This can be done through majlis taklim or other studies. Other efforts that can be done are preventive, educative, curative and rehabilitative